Effect of oral glucosamine on joint structure in individuals with chronic knee pain: a randomized, placebo-controlled clinical trial - Kwoh, C. Kent; Roemer, Frank; Hannon, Michael J.; Moore, Carolyn E.; Jakicic, John M.; Guermazi, Ali; Green, Stephanie M.; Evans, Rhobert W.; Boudreau, Robert (Arthritis and Rheumatology, 2014)
To determine the short-term efficacy of oral glucosamine supplementation by evaluating structural lesions in the knee joints, as assessed using 3T magnetic resonance imaging (MRI).This study was designed as a randomized, double-blind, placebo-controlled trial. Recruitment was performed via mass mailings and an arthritis registry in southwestern Pennsylvania. In total, 201 participants with mild-to-moderate pain in one or both knees, as defined by a Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) pain score >=25 and <=100, were enrolled. Of these subjects, 69.2% had a Kellgren/Lawrence grade >=2 in at least 1 knee. Participants received 24 weeks of treatment with 1,500 mg glucosamine hydrochloride in beverage form or a placebo beverage. The primary outcome was decreased worsening of cartilage damage on 3T MRI of both knees, assessed according to a validated scoring system, the Whole-Organ MRI Score (WORMS). Secondary outcomes included change in bone marrow lesion (BML) scores in all knees and change in excretion of urinary C-terminal crosslinking telopeptide of type II collagen (CTX-II).The adjusted odds ratio (OR) for the likelihood of decreased cartilage damage over 24 weeks in any WORMS-scored subregion of the knee in the glucosamine treatment group compared to the control group was 0.938 (95% confidence interval [95% CI] 0.528, 1.666). Compared to subjects treated with glucosamine, control subjects showed more improvement in BMLs (adjusted OR 0.537, 95% CI 0.291, 0.990) but no difference in worsening BMLs (adjusted OR 0.691, 95% CI 0.410, 1.166) over 24 weeks. There was no indication that treatment with glucosamine decreased the excretion of urinary CTX-II (? = -0.10, 95% CI -0.21, 0.002).The results of this short-term study provide no evidence of structural benefits (i.e., improvements in MRI morphologic features or urinary CTX-II excretion) from glucosamine supplementation in individuals with chronic knee pain.
EVALuna2:14575